Peran Pendidikan Agama Islam pada Stabilitas Emosional Remaja Menuju Dewasa - Rusyda Makitsuna S.A; Mohammad Zakki Azani (Universitas Muhammadiyah Surakarta, 2026)
This study aims to analyze the role of Islamic Religious Education (IRE) in maintaining the emotional stability of adolescents aged 15–17. Using a descriptive qualitative method, data were collected through interviews with three adolescents currently enrolled in IRE and supplemented with documentation techniques. The findings indicate that IRE values have a direct impact on adolescents’ emotional regulation; for instance, an understanding of qada and qadar helps them cope with failure, worship provides psychological calm, moral conduct strengthens self-control, and tawakal fosters optimism about the future. Although the application of these values still faces external challenges such as social pressure and digital media, PAI has proven to be important in strengthening adolescents’ mental health, emotional stability, and character.